Decision Support System For Election Suppliers of Goods Using The Simple Method Additive Weighting (SAW) - Aprilandri, Gusti; Rumini, Rumini; Maulina, Dina (Mobile and Forensics, 2024)
Selection of suppliers of goods is the main key to starting a retail business. The market will find it difficult to determine suppliers because it will have a big effect on the final selling price. The Diva Shop is a medium-sized business that is still growing in the city. The system run by the store is still running on experience. As a store that is ready to compete, the store needs a supporting design system in determining the selection of suppliers of goods. The system is run using the Simple Additive Weighting (SAW) method. That The system that will be created uses the criteria that will be applied by the user based on the SAW method. The SAW design method uses a weighted summation method with the accumulation of various data, each value from the weight results obtained becomes the final decision. The Simple Additive Weighting (SAW) method can be applied properly and correctly to the decision support system at the Diva Store. The steps and results of calculations manually are the same as the steps and results of calculations performed by the system. For testing applications based on the Confusion Matrix method, the accuracy is 73.77% with an error percentage of 26.23%.